2022
DOI: 10.5194/nhess-22-1499-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effective uncertainty visualization for aftershock forecast maps

Abstract: Abstract. Earthquake models can produce aftershock forecasts, which have recently been released to lay audiences. While visualization literature suggests that displaying forecast uncertainty can improve how forecast maps are used, research on uncertainty visualization is missing from earthquake science. We designed a pre-registered online experiment to test the effectiveness of three visualization techniques for displaying aftershock forecast maps and their uncertainty. These maps showed the forecasted number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Poor data visualization can contribute to ineffective or subpar science communication, as highlighted by Padilla (2022), who discusses the challenges of conveying uncertainty through maps and emphasizes the need for effective visualization strategies to enhance comprehension of these uncertainties. Clear and accurate representation of uncertainty is relevant for many geoscientific challenges such as aftershock forecast maps (Schneider et al, 2022). The incorrect use of color in data visualization, as highlighted in Crameri et al (2020), can also lead to misinterpretation of information.…”
Section: Poor Quality and Lack Of Rigormentioning
confidence: 99%
“…Poor data visualization can contribute to ineffective or subpar science communication, as highlighted by Padilla (2022), who discusses the challenges of conveying uncertainty through maps and emphasizes the need for effective visualization strategies to enhance comprehension of these uncertainties. Clear and accurate representation of uncertainty is relevant for many geoscientific challenges such as aftershock forecast maps (Schneider et al, 2022). The incorrect use of color in data visualization, as highlighted in Crameri et al (2020), can also lead to misinterpretation of information.…”
Section: Poor Quality and Lack Of Rigormentioning
confidence: 99%
“…Moreover, pre-existing instrumentation may be sparse owing to inadequate seismic awareness (e.g., no recorded history of damaging seismic events), regional inaccessibility, or political instability and lack of funding. In turn, the sparsity of instrumentation and seismic data negatively impacts the confidence bounds on aftershock forecasts, which is a necessary aspect of hazard communication (Michael et al, 2020;Schneider et al, 2022).…”
Section: Overviewmentioning
confidence: 99%
“…lower confidence in the hazard at Hilo because of green color in Figure 9a versus yellow color in Figure 9b). In the context of aftershock forecast maps, Schneider et al (2022) found that showing the lower/upper bounds was more effective than the other two approaches at communicating ''potential surprise'' locations (i.e. locations where high uncertainty could lead to worse outcomes than predicted).…”
Section: Hazard Examplementioning
confidence: 99%
“…Researchers have examined various ways to visualize uncertainties in a map (e.g. Schneider et al, 2022). For instance, one way is to plot the central estimates (e.g.…”
Section: Uses Of Fractile Hazard Curvesmentioning
confidence: 99%